Message from Editors-in-Chief - Hirota, Kaoru; Fukuda, Toshio (Journal of advanced computational intelligence and intelligent informatics, 2017)
It is our great pleasure to congratulate the Journal of Advanced Computational Intelligence and Intelligent Informatics (JACIII) on its 20 th anniversary. The concept of Computational Intelligence was originally authorized in the first IEEE World Congress on Computational Intelligence (WCCI) held in Orlando, Florida in 1994, where the key issues of CI were characterized by fuzzy, neuro, and EC (Evolutionary Computation). The JACI (Journal of Advanced Computational Intelligence) Vol.1 No.1 was published from Fuji Technology Press in Oct 1997, and the name of the journal has been changed to JACIII since Vol.7 No.1 Feb 2003 to accept more widely developed issues related to intelligent informatics.   The JACIII is currently published in bimonthly, six issues a year, in cooperation with International Fuzzy Systems Association (IFSA), Japan Society for Fuzzy Theory and Intelligent Informatics (SOFT), Brazilian Society of Automatics (SBA), The Society of Instrument and Control Engineers (SICE), John von Neumann Computer Society (NJSZT), Vietnamese Fuzzy Systems Society (VFSS), Fuzzy Systems and Intelligent Technologies Research Society of Thailand (FIRST), Korean Institute of Intelligent Systems (KIIS), and Taiwanese Association for Artificial Intelligence (TAAI), and is indexed in ESCI, SCOPUS, and COMPENDEX (Ei-Index).   In the past 20 years personally, so many issues happened in the JACIII editing process. Some of them were very tough but all are very good memories to us. We occasionally organize the JACIII editorial meetings in Tokyo and remotely. As Editors-in-Chief, we are most grateful to all who have worked with the JACIII and helped reach its 20 th anniversary. We thank the editorial board members for editing this journal with their high discernment and the guest editors for arranging special issues with their high profession. We would also like to thank the peer reviewers for their accurate evaluations in a short time, and finally our special thanks go to the editorial office of Fuji Technology Press Ltd., especially to its founder, Mr. K. Hayashi, and to the editors, Ms. Reiko Ohta and Mr. Kunihiko Uchida for their efforts in publishing this journal.